Well-Differentiated Neuroendocrine Tumor of the Appendix - Durry, Meilany Feronika; Lintong, Poppy Magdalena (Gaceta Médica de Caracas, 2022)
Appendiceal Neuroendocrine Tumors (NET) comprise rare tumors of the appendix, mainly affecting young populations and characterized by a rather favorable prognosis. Appendiceal NET is either asymptomatic or present as acute appendicitis, which is then diagnosed incidentally during surgery. We reported the case of a 9-year-old girl presenting with the common appendicitis symptoms of fever and abdominal pain.